(untitled) (Journal of Engineering, 2021)
Recently times, industrial development has increased, including plastic industries, and since plastic has a very long analytical life, it will cause environmental pollution. Therefore studies have resorted to reusing recycled plastic waste (sustainable plastic) to produce environmentally friendly concrete (green concrete). In this research, some studies were reviewed and then summarized into several things, including the percentage of plastic replacement from the aggregate and the effect of this percentage on the fresh properties of concrete, such as the workability and the effect of plastic waste on the hardening properties of concrete such as dry density, compressive, tensile and flexural strength.